Incidence of visual impairment due to cataract, diabetic retinopathy and trachoma in indigenous Australians within central Australia: the Central Australian Ocular Health Study. (29th October 2012) - Landers, John; Henderson, Tim; Craig, Jamie E
Abstract : Background: To estimate the incidence and causes of visual impairment for the purposes of service provision among the indigenous Australian population within central Australia from its most common causes, namely cataract, diabetic retinopathy and trachoma. Design: Clinic‐based cohort study. Participants: One thousand eight hundred eighty four individuals aged ≥20 years living in one of 30 remote communities within the statistical local area of 'Central Australia'. Methods: From those initially recruited, 608 (32%) participants were reviewed again between 6 months and 3 years (median 2 years). Patients underwent Snellen visual acuity testing and subjective refraction. Following this, an assessment of their anterior and posterior segments was made. Baseline results were compared with those who were reviewed. Main Outcome Measures: The annual incidence rates and causes of visual impairment (vision worse than Snellen visual acuity 6/12 in at least one eye). Results: The incidence of visual impairment in at least one eye was 6.6%, 1.2% and 0.7% per year for cataract, diabetic retinopathy and trachoma, respectively (7.9%, 1.5% and 0.7% per year for those aged ≥40 years). Advancing age was the main risk factor common to all three. Conclusion: It is important to be mindful not only of the prevalence of disease in a community but also of the rate at which new cases are occurring when allocating resources to address the ocular health needs of this region. Compared with historical data, diabetic retinopathy is emerging as a new and increasing threat to vision in this population.